GLOCALIZATION APPROACHES IN LANGUAGE AND MEDIA IN LIBRARY INFORMATION SYSTEMS: AN IMPACT ANALYSIS ON USER ENGAGEMENT - Nur Husniyatul Adyani; Mega Alif Marintan (2024)
The emergence of the concept of glocalization is a process of adaptation of global products to local markets and cultures. Glocalization significantly influences the quality of the community's political, economic, social, and cultural life to foster innovations in information from various contexts. As one of the information provider institutions, the library has a role in balancing and providing facilities for the information needs of both local and global communities, such as information systems to the community to increase regional productivity using technology. This study intends to identify the principles of the glocalization approach in language and media in library information systems, analyze the most effective strategies to integrate global elements of local values through library information systems, as well as the impact of user engagement to minimize user linguistic challenges in the concept of glocalization in their services with a focus on adapting language diversity in various media. This research is based on the idea of glocalization with the principles of inclusion and accessibility in the information system of a library. This study uses a descriptive qualitative method with a case study approach. Data was collected through interviews with librarians, library user surveys, participatory observations, and library information system usage analysis. A case study was conducted at the Dinas Perpustakaan dan Kearsipan Kota Surakarta, explaining the impact of globalization on library systems and services. The results showed that glocalization approaches in language and media in library information systems significantly impact users' linguistic challenges. Libraries can develop innovations regarding information systems by applying the principle of glocalization, such as language adjustments in the user interface, as well as the use of media by local preferences.